Rocket Measurements of Daytime Electron Density and Temperature Profiles in the Polar Ionosphere - Ogawa, Tadahiko; Mori, Hirotaka; Miyazaki, Shigeru (1978)
P(論文) Two sounding rockets, S-210JA-22 and S-310JA-1,were successfully launched into the quiet daytime ionosphere from Syowa Station, Antarctica in the summer of 1976 for measuring electron density and temperature. The S-210JA-22 experiment shows that the E-region electron density (N_e) was nearly 2×(10)^4/(cm)^3 and that the electron temperature (T_e) increased with altitude, being 600±200K at altitude of 100km to 900±300K at 120km. Profiles between 90 and 215km measured by S-310JA-1 reveal that N_e changed slowly from 1×(10)^5 at 100km to 7×(10)^4/(cm)^3 at 215km and that T_e had a minimum of 500±100K at 110km which was followed by the gradual increase attaining to 1900±200K at 215km. Comparing the present results with the daytime electron density profiles obtained at Syowa Station during 1970-1973 and with those at mid-latitude, it is pointed out that main ionization process occurring in the polar D-region is a high energy particle precipitation from the magnetosphere even under quiet daytime ionospheric conditions. departmental bulletin paper